Pengaruh Struktur Kepemilikan terhadap Struktur Modal: Analisis Time-Series Cross-Sectional - Nurbaiti, Nurbaiti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2006)
The purpose of this study is to identify the impact of ownership structure on capital structure. Based on agency theory by Jensen and Meckling (1976) that there is conflict of interest between managers and owners because managers act opportunisticly. Previous research based on agency theory found shows that insiders of shareholders and institutional investors have role in decreasing agency cost, because they can substitute the role of debt for the disciplinary insider’s acts in a corporate capital structure. Samples were selected by using purposive sampling to all companies of the manufacture industry listed in Jakarta Stock Exchange one year before sample year (1999-2002). Achieving this purposes, the multiple regression model was used by analyzing 155 observed firms from manufacturing companies. The F-statistic test shows that variables of ownership structure consisted of insiders ownership, institutional ownership and shareholders dispersion while control variable consisted offirm size, firm profitability, firm growth, assets structure, tax rate, and stock volatility simultaneously influence capital structure. The partially test shows that the ownership structure with proxy shareholders dispersion has a positive and significant affect on capital structure. The firm profitability and tax rate variables control have significantly affected the capital structure. The study has different results compared with the study Moh’d, et al. (1998) on the fact that the dispersion ownership on manufacture industry in Jakarta Stock Exchange exist during the study period. This fact causes owner to improve debt role in corporate capital structure to discipline insiders act. Keywords: Ownership structure, agency theory, agency cost, and capital structure